Enantioselective Trifluoromethylthiolating Lactonization Catalyzed by an Indane-Based Chiral Sulfide - Liu, Xiang; An, Rui; Zhang, Xuelin; Luo, Jie; Zhao, Xiaodan (Angewandte Chemie International Edition, 2016)
Enantioselective trifluoromethylthiolation, especially of alkenes, is a challenging task. In this work, we have developed an efficient approach for enantioselective trifluoromethylthiolating lactonization by designing an indane‐based bifunctional chiral sulfide catalyst and a shelf‐stable electrophilic SCF3 reagent. The desired products were formed with diastereoselectivities of >99:1 and good to excellent enantioselectivities. The transformation represents the first enantioselective trifluoromethylthiolation of alkenes and the first enantioselective trifluoromethylthiolation that is enabled by a catalyst with a Lewis basic sulfur center. An efficient approach for enantioselective trifluoromethylthiolating lactonization entails the use of an indane‐based bifunctional chiral sulfide catalyst and a new shelf‐stable electrophilic SCF3 reagent. This transformation represents the first enantioselective trifluoromethylthiolation that is enabled by a catalyst with a Lewis basic sulfur center.